The Status of Meaningful Human Control of Lethal Autonomous Weapons System in International Humanitarian Law - Zhu, Lijiang; Hu, Xinyi; Han, Yutong (Faculty of Law, Universitas Brawijaya, 2025)
Meaningful human control (MHC) has become a central topic in the discussions of the Group of Governmental Experts (GGE) on lethal autonomous weapons systems (LAWS) under the Convention on Certain Conventional Weapons (CCW), as it addresses the “accountability gap” these systems may generate. Nevertheless, its status under international humanitarian law (IHL) is unclear. Therefore, it is imperative to clarify its status in IHL. Through an international law source analysis methodology, this paper concludes that, at the conventional-international-law level, MHC can be inferred through a systemic interpretation of 1977 Additional Protocol I to the Geneva Conventions (API). Article 36 of API obliges States to determine the legality of new weapons in all circumstances, while Article 57 of API requires attackers to take all feasible precautions. At the customary-international-law level, although MHC has received wide support from many States and organizations, the reservations of several major powers, such as the United States, and the conceptual divergences hinder the emergence of consistent state practice and opinio juris. However, those major powers, though cautious, have not explicitly rejected the notion of “human control” and thus cannot be regarded as persistent objectors. Finally, at the general-principles-of-law level, the Martens Clause provides normative orientation and moral legitimacy, but its abstract nature prevents it from serving as an autonomous legal basis for MHC.